STRATEGI KOMISI PEMILIHAN UMUM KABUPATEN MANGGARAI DALAM MENINGKATKAN PARTISIPASI PEMILIH DALAM PEMILIHAN UMUM TAHUN 2024 - Bili Agus, Yosefiani Margaretha; Yohanes, Saryono; Ratu Udju, Hernimus (Petitum Law Journal, 2025)
This study examines the efforts of the General Election Commission of Manggarai Regency to increase voter turnout for the 2024 Election through fact-based legal strategies. Data were gathered via interviews and document analysis at the KPU Manggarai office. The study identified six key steps: (1) technological voter data management (WhatsApp, Sidalih); (2) inclusive registration (e-KTP access, Voting Rights Guard Post); (3) diverse socialization channels (Goes to School/Campus, social media, billboards); (4) political education targeting new voters, women, and persons with disabilities; (5) creative programs (e.g., Colour Run) and inter-institutional collaboration; and (6) accessible polling stations (facilities for the elderly and disabled, Braille templates). Despite these efforts, four main obstacles emerged: (a) limited human resources (Pantarlih competence); (b) infrastructure issues (road access, polling station shortages, weak electricity/network); (c) unbalanced budget allocation (only 0.35% or IDR 161 million for socialization out of IDR 45.3 billion); and (d) suboptimal participation (average 75.36%, below the 80% national target). Gaps between electoral districts (lowest in District 3: 73.39%) and minimal DPK/DPTb usage highlight persistent challenges related to geography, administration, and resource limitations.